Coating composition, coat layer containing the same, and molded article

JP2024028550A5Active Publication Date: 2025-03-12KJ CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024007158
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-11
Filing Date
2024-01-22
Publication Date
2025-03-12
Estimated Expiration
2042-03-07

AI Technical Summary

Technical Problem

Conventional adhesives and coating compositions for resin products, such as polyimide films, fail to provide sufficient adhesion, blister resistance, and surface hardness, leading to issues like peeling and poor flexibility, making them unsuitable for flexible and durable applications in electronic devices.

Method used

A coating composition comprising an acrylic polymer with branched alkyl or alkenyl groups and a polymerizable compound, which can form non-adhesive or adhesive layers through thermal or light-activated polymerization, offering improved adhesion, flexibility, and durability on resin substrates.

Benefits of technology

The composition achieves high adhesion, flexibility, and durability, with enhanced surface hardness, scratch resistance, and transparency, suitable for resin substrates like polyimide films, enabling applications in optical and electronic devices.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a coating composition which enables formation of a non-adhesive coat layer that has good adhesion to various resin substrates, and excellent surface hardness, tack resistance, bending resistance, scratch resistance, shrinkage resistance and moist heat resistance and / or an adhesive coat layer having excellent adhesion, stickiness, transparency, stain resistance, moist heat resistance, resistance against yellow discoloration and step followability, a non-adhesive coat layer and an adhesive coat layer formed of the coating composition, various laminates having the coat layer on one surface or both surfaces of the substrate, a cover film, and a substrate.SOLUTION: A coating composition contains 0.5-30.0 mass% of an acrylic polymer (A) having a branched alkyl group having 3 to 20 carbon atoms and / or a branched or non-branched alkenyl group at a side chain, and 70.0-99.5 mass% of a polymerizable compound (B).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating composition, an adhesive or non-adhesive coating layer comprising the coating composition, and a laminate comprising these coating layers. [Background technology]

[0002] Thin plate glass (glass substrate) excellent in transparency, hardness, heat resistance, etc. has been used as a surface material for displays, a touch panel member, and a material for electronic devices such as liquid crystal display devices and organic electroluminescence display devices. For example, glass substrates are used as display element substrates for displays in which various electronic elements such as thin transistors and transparent electrodes are formed on the glass substrate, and as cover substrates having a protective function that are placed on the surface of displays. In addition, adhesives are used to fix laminates of various optical films to glass substrates of liquid crystal display (LCD) cells in order to improve the display quality of the display, and adhesives are also used to prevent the cover glass, which has a protective function, from cracking and to prevent it from scattering when it is cracked.

[0003] However, glass substrates have problems in workability and operability, such as being difficult to bend and easily broken, and are also heavy compared to plastic products. Therefore, in order to strengthen the impact resistance of the panel itself, make it flexible, thin, and lightweight, resin products such as resin substrates and resin films are replacing glass products, and research has been conducted on resin products that can be used as glass substitutes from the viewpoints of workability and weight reduction. In particular, fluororesin films and polyimide films, which have excellent heat resistance, dimensional stability, and insulating properties, are actively used as insulating materials for electronic components, such as chip coating films in semiconductor elements and substrates for flexible printed wiring boards, and in recent years, research on resin products using polyimide resins with improved transparency as glass substitutes has been particularly attracting attention.

[0004] On the other hand, when using resin products, such as a film of a resin substrate (also referred to as a substrate film or resin film), a sheet of a resin substrate (also referred to as a substrate sheet or resin sheet), or a substrate of a resin substrate (also referred to as a substrate substrate or resin substrate), it is necessary to use an adhesive between a resin sheet for a display element and an optical film laminate, or between resin products such as a resin film, a resin sheet, or a resin substrate for the purpose of fixing a resin substrate for a cover (for surface protection), but the conventional inexpensive and easy-to-handle acrylic adhesive does not have sufficient adhesion to these resin products, and new problems such as unsatisfactory blister resistance and reworkability have arisen. In particular, fluororesin films and polyimide films have a significant disadvantage of being incompatible with general-purpose adhesives and adhesive layers formed from adhesives, and are difficult to adhere to, making it difficult to put them into practical use. In addition, when these resin products are used as cover substrates or cover films having a protective function, they have excellent processability as materials for flexible display devices, but they have insufficient performance in terms of surface hardness and scratch resistance, so they have not been put into practical use.

[0005] It has been proposed to provide a hard coat layer on the surface (one or both sides) of a polyimide film in order to protect the surface of a resin substrate such as a polyimide film and to improve the surface hardness and scratch resistance. For example, Patent Document 1 proposes applying a coating liquid consisting of a multifunctional acrylate and a photoinitiator to the surface of a polyimide film and forming a hard coat layer by irradiating ultraviolet rays. Patent Document 2 proposes applying a resin composition consisting of a urethane acrylate-based hard coat agent having a benzene ring content of 50% by mass or more and a hard coat agent having an epoxy skeleton to the surface of a polyimide film and forming a hard coat layer by photocuring.

[0006] However, the cured layer disclosed in Patent Document 1 is likely to form a hard coat layer with a high crosslink density by photopolymerization of a multifunctional acrylate, and while the surface hardness of the polyimide film is improved, there is a problem that the adhesion between the hard coat layer and the polyimide film is poor. As a result, when used as a flexible material, there is a high possibility that cracks will occur in the hard coat layer due to repeated bending, and the hard coat layer will peel off from the polyimide film. On the other hand, the hard coat layer disclosed in Patent Document 2 is for protecting the polyimide film, and although it is disclosed that it has good adhesion to the aromatic polyimide film, there is no mention of the surface hardness, scratch resistance, and bending resistance (bending resistance) of the obtained polyimide film laminate. In addition, since the resin composition for the hard coat layer in Patent Document 2 has more than half (content 50% by mass) of rigid benzene ring structures, it is clear that it is not applicable to the formation of a flexible coat layer.

[0007] In addition, since poorly adhesive materials such as polyimide have low adhesion to general-purpose coating compositions and coating agents, and low adhesion to other materials, techniques using surface modifiers (wet etching) and techniques combining wet etching and ultraviolet light irradiation have been studied for the purpose of improving the adhesion of film-like or sheet materials. For example, Patent Document 3 describes a technique in which a surface modifier containing an amino alcohol and an ammonium salt is applied to a polyimide film to improve the adhesion of the film surface. Patent Document 4 describes a technique in which a polyimide film is wet-etched with hydrogen peroxide or hypochlorous acid, and then irradiated with ultraviolet light having a wavelength of 170 nm to 360 nm to modify the polyimide film surface. Patent Document 5 describes a technique in which a KrF excimer laser having a wavelength of about 250 nm is irradiated in the presence of a first oxidizing agent such as oxygen or ozone, and then an etching treatment is performed with a second oxidizing agent such as permanganate to modify the surface of the polyimide film.

[0008] However, wet etching alone does not improve the adhesion of the polyimide film, and there is a problem that the film cannot be used stably for a long period of time. In addition, the combination of etching and ultraviolet irradiation requires a chemical treatment process such as etching and a process of ultraviolet irradiation before providing an adhesive layer, which makes the operation complicated and requires a special device that generates a high-power laser. Furthermore, the irradiation of high-power laser light may cause partial deterioration not only of the surface of the polyimide film but also of the inside, and there remains a concern of a decrease in durability when considering application to optical and electronic devices.

[0009] Thus, it has been difficult for the polyimide film and polyimide film laminate modified using the conventional photocurable resin composition for hard coat to achieve both rigid properties such as surface hardness and scratch resistance and flexible properties such as flexibility and bending resistance. A film laminate that can achieve both rigidity and flexibility and further has adhesion between a coating layer formed from a photocurable resin composition and a substrate film such as a polyimide film has not yet been proposed. In addition, in various resin films, resin sheets, and resin substrates including fluororesins and polyimides, there is a demand for coating compositions, pressure-sensitive adhesive compositions, and pressure-sensitive adhesive layers that do not require excessive treatment or modification of the surfaces of these resin materials and have good adhesion to the resin surface while maintaining the original properties of the resin materials. In particular, pressure-sensitive adhesive layers and pressure-sensitive adhesive sheets that can achieve both high adhesion and blister resistance to various display element substrates and cover substrates, and various substrate films and sheets used for laminating optical films, and that have excellent step following properties, moisture and heat resistance, and weather resistance are expected. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Special Publication No. 2016-501144 [Patent Document 2] JP 2018-192699 A [Patent Document 3] JP 2003-192811 A [Patent Document 4] Japanese Patent Application Publication No. 11-293009 [Patent Document 5] Japanese Patent Application Publication No. 9-157417 Summary of the Invention [Problem to be solved by the invention]

[0011] In view of the problems of the conventional techniques described above, the present invention has an object to provide a coating composition capable of forming a coating layer having good transparency, yellowing resistance and curability, excellent surface hardness, tack resistance, scratch resistance, bending resistance, shrinkage resistance and moist heat resistance, and having excellent adhesion to various resin films, resin sheets and resin substrates including fluororesins and polyimides; a non-adhesive coating layer and an adhesive coating layer (adhesive layer) formed from the coating composition; and various laminates and molded articles for optical or electronic devices having the coating layer on one or both sides of various resin substrates (films, sheets, plates, etc.). [Means for solving the problem]

[0012] As a result of intensive research to solve the above problems, the inventors have found that a coating composition containing 0.5 to 30.0 mass% of an acrylic polymer (A) having a branched alkyl group and / or a branched or unbranched alkenyl group having 3 to 20 carbon atoms in its side chain, and 70.0 to 99.5 mass% of a polymerizable compound (B) can be applied to various resin substrates and polymerized by heat polymerization and / or polymerization with active energy rays such as light to obtain a non-adhesive coating layer or an adhesive coating layer that satisfies the above-mentioned properties, and that the desired laminates, molded articles, etc. can be obtained by providing these coating layers on one or both sides of a substrate, thereby completing the present invention.

[0013] That is, the present invention provides: (1) A coating composition comprising: 0.5 to 30.0 mass% of an acrylic polymer (A); and 70.0 to 99.5 mass% of a polymerizable compound (B), wherein the acrylic polymer (A) has a branched alkyl group having 3 to 20 carbon atoms and / or a branched or unbranched alkenyl group in a side chain; (2) The coating composition according to (1), wherein the acrylic polymer (A) has a weight average molecular weight of 100,000 to 6,000,000 and a glass transition temperature (Tg) of −85° C. to 40° C. (3) The coating composition according to (1) or (2), wherein the acrylic polymer (A) is (A1) further having an active hydrogen-containing functional group (R1) in a side chain, (A2) further having a functional group (R2) reactive with the active hydrogen-containing functional group (R1) in a side chain, and / or (A3) further having a (meth)acryloyl group or an unsaturated alicyclic hydrocarbon group in a side chain. (4) The coating composition according to any one of (1) to (3), characterized in that the polymerizable compound (B) contains a monofunctional acrylic monomer (b1) and a polyfunctional acrylic monomer (b2), and the content of (b1) is 10.0 to 96.0 mass% based on the total amount of the coating composition, and the content of (b2) is 0 to 80.0 mass% based on the total amount of the coating composition. (5) The coating composition according to any one of (1) to (4), wherein the polymerizable compound (B) further contains a urethane oligomer (b3) (excluding b1 and b2), and the content of (b3) is 2.0 to 50.0 mass% based on the total amount of the coating composition. (6) The coating composition according to (5) above, wherein the urethane oligomer (b3) is a urethane (meth)acrylamide oligomer. (7) A non-adhesive coating layer obtained by polymerizing the coating composition according to any one of (1) to (6) above with light and / or heat. (8) An adhesive coating layer obtained by polymerizing the coating composition according to any one of (1) to (6) above with light and / or heat. (9) A pressure-sensitive adhesive sheet having the coating layer according to (7) or (8) on one or both sides of a film-like and / or sheet-like substrate. (10) A laminate having the coating layer according to (7) or (8) on one or both sides of a film-like and / or sheet-like substrate. (11) An optical laminate having the coating layer according to (7) or (8) on one or both sides of a film-like and / or sheet-like substrate, and having a total light transmittance of 80% or more. (12) A laminate for flexible devices comprising the coating layer according to (7) or (8) on one or both sides of a film-like and / or sheet-like substrate. (13) A surface protective laminate comprising the coating layer according to (7) or (8) on one or both sides of a film-like and / or sheet-like substrate. (14) A laminate for a display comprising the coating layer according to (7) or (8) on one or both sides of a film-like and / or sheet-like substrate. (15) The laminate according to any one of (10) to (14), wherein the film-like substrate is any one of films selected from a polyester film, a polycarbonate film, a fluororesin film, a polyimide film, a triacetyl cellulose film, an acrylic film, a polystyrene film, a polyvinyl chloride film, a polyvinyl alcohol film, and a nylon film. This provides: Effect of the Invention

[0014] The coating composition of the present embodiment contains an acrylic polymer (A) and a polymerizable compound (B) as essential components. The acrylic polymer (A) has a branched alkyl group having 3 to 20 carbon atoms and / or a branched or unbranched alkenyl group in the side chain, so that the coating layer itself has flexibility and water resistance in both the non-adhesive coating layer and the adhesive coating layer (adhesive layer) formed from the coating composition, and the bending resistance and moist heat resistance of various laminates and molded products having such a coating layer are improved. In addition, by combining the acrylic polymer (A) and the polymerizable compound (B), the coating composition shows excellent affinity (wettability) and adhesion to general-purpose resin substrates such as polyesters and polycarbonates, as well as to poorly adhesive fluororesin and polyimide substrates.

[0015] Furthermore, the polymerizable compound (B) can be used as a raw material monomer for the acrylic polymer (A). In this case, even if the acrylic polymer (A) has a high molecular weight, it can be dissolved uniformly and stably in the polymerizable compound (B) at the molecular level, and a coating composition with extremely high transparency and a coating layer with good transparency and yellowing resistance can be obtained, so that the acrylic polymer can be suitably used as an optical member or an electronic device member.

[0016] Furthermore, it is preferable to use a (meth)acrylamide-based monomer as both the raw material monomer of the acrylic polymer (A) and the polymerizable compound (B). When a (meth)acrylamide-based monomer is used as the raw material monomer of the acrylic polymer (A), a large number of amide groups are present in the side chain of A, and a strong cohesive force is generated between the amide groups, and the adhesion of the obtained coating layer is further improved by this cohesive force and the interaction between the hydrophilic amide group and the hydrophobic main chain of A, and there is a feature that no adhesive residue or contamination of the adherend occurs when the adhesive coating layer is reworked. In addition, when a (meth)acrylamide-based monomer is used as the polymerizable compound (B), the polymerization of B is good, and the polymerization and curing properties of the coating composition are high. Furthermore, since the glass transition temperature of the homopolymer of the (meth)acrylamide-based monomer is high, there is a feature that the obtained non-adhesive coating layer has excellent surface hardness, tack resistance, and scratch resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described in detail. The first embodiment of the present invention is a coating composition (D). The coating composition (D) according to this embodiment is a composition containing an acrylic polymer (A) having a branched alkyl group and / or a branched or unbranched alkenyl group having 3 to 20 carbon atoms in the side chain and a polymerizable compound (B). The coating composition (D) can form a coating layer by polymerization by heat (thermal polymerization), polymerization by active energy rays such as light (photopolymerization), or polymerization by a combination of thermal polymerization and photopolymerization (hybrid polymerization). The coating composition can be applied to one or both sides of a film-like or sheet-like substrate and then polymerized by the various polymerization methods described above to form a coating layer. In addition, the coating composition can be polymerized by the various polymerization methods described above, and then applied to one or both sides of a film-like or sheet-like substrate in the form of a solid such as a powder or in the form of a solution in the presence of a solvent or a polymerizable compound, and then treated with active energy rays such as electricity, heat, or light to form a coating layer. Furthermore, by adjusting the composition of the coating composition, it is possible to easily obtain a non-adhesive coating layer to be applied for surface protection or as a top coat, and an adhesive coating layer to be used as an adhesive or a pressure sensitive adhesive layer.

[0018] The second embodiment of the present invention is a coating layer having a crosslinked structure obtained by curing the coating composition (D). The crosslinked structure of the coating layer can be formed by thermal polymerization of a branched or unbranched alkenyl group (ethylenically unsaturated bond) having 3 to 20 carbon atoms present in the side chain of the acrylic polymer (A) with a polymerizable compound (B), polymerization by active energy rays such as light, or hybrid polymerization. In the case of a non-adhesive coating layer, the surface hardness, strength, scratch resistance, etc. of the coating layer increase with an increase in crosslink density, and the coating layer is preferably used as a top layer coating film or a surface protective layer coating film, so that the coating layer is preferably a crosslinked non-adhesive coating layer. On the other hand, in the case of an adhesive coating layer, the formation of a crosslinked structure improves blister resistance, weather resistance, heat resistance, and substrate contamination resistance, so that the coating layer is preferably a crosslinked adhesive coating layer.

[0019] The acrylic polymer (A) may further have an active hydrogen-containing functional group (R1) or a functional group (R2) that reacts with the active hydrogen-containing functional group (R1) in the side chain, and these are referred to as acrylic polymer (A1) and acrylic polymer (A2), respectively. The acrylic polymer (A), acrylic polymer (A1) and acrylic polymer (A2) may be used alone or in combination of two or more. When the acrylic polymer (A1) is used in the coating composition, if the polymerizable compound (B) contains a reactive functional group (R2), a crosslinked structure can be formed by thermal polymerization, polymerization or hybrid polymerization by active energy rays such as light, and a chemical reaction between the acrylic polymer (A1) and the polymerizable compound (B) (a chemical reaction between the functional group (R1) and the functional group (R2)). Similarly, when the acrylic polymer (A2) is used, if the polymerizable compound (B) contains the functional group (R1), a crosslinked structure can be formed. Examples of the functional group (R1) having an active hydrogen include a hydroxyl group, a thiol group, an amino group, and a carboxyl group, and examples of the functional group (R2) that reacts with R1 include an isocyanate group and a glycidyl group.

[0020] The acrylic polymer (A) may have a (meth)acryloyl group or an unsaturated alicyclic hydrocarbon group in the side chain, which is referred to as the acrylic polymer (A3). The (meth)acryloyl group or the unsaturated alicyclic hydrocarbon group may be brought in from the raw material monomer of the acrylic polymer (A3), or may be introduced via the functional group (R1) or (R2) after the synthesis of the acrylic polymer (A). When the acrylic polymer (A3) is used in the coating composition, a crosslinked structure can be formed by thermal polymerization, polymerization by active energy rays such as light, or hybrid polymerization.

[0021] Examples of raw material monomers for the acrylic polymer (A) include (meth)acrylic monomers having a branched alkyl group having 3 to 20 carbon atoms and / or a branched or unbranched alkenyl group.

[0022] The (meth)acrylic monomer, which is the raw material of the acrylic polymer (A), may be a monomer having one type of unsaturated bond selected from a methacrylate group, an acrylate group, a methacrylamide group, and an acrylamide group in one molecule. Among the unsaturated bonds, a monomer having one type selected from an acrylate group, a methacrylate group, and an acrylamide group is preferable from the viewpoint of easily obtaining a polymer having a relatively low glass transition temperature (hereinafter sometimes abbreviated as Tg).

[0023] Examples of the branched alkyl group having 3 to 20 carbon atoms include an isopropyl group, a sec-butyl group, a tert-butyl group, an isobutyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,1-dimethylpropyl group, a 1,1-dimethylbutyl group, a 2,2-dimethylbutyl group, a 3,3-dimethylbutyl group, a 2-ethylbutyl group, an isooctyl group, a tert-octyl group, a 2-ethylhexyl group, and an isodecyl group.

[0024] Examples of the branched or unbranched alkenyl group having 3 to 20 carbon atoms include an allyl group, a 1-propenyl group, a 2-propenyl group, a 2-methyl-1-propenyl group, a 1-butenyl group, a 2-butenyl group, a 3-butenyl group, a 3-methyl-2-butenyl group, a 1,3-butadienyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, a 4-pentenyl group, a 4-methyl-3-pentenyl group, a 1-hexenyl group, a 2-hexenyl group, a 3-hexenyl group, a 5-hexenyl group, a heptenyl group, an octenyl group, a nonenyl group, a decenyl group, an undecenyl group, a dodecenyl group, a tetradecenyl group, a hexadecenyl group, an octadecenyl group (oleyl group), an eicosenyl group, and a docosenyl group.

[0025] The (meth)acrylic monomer that is the raw material of the acrylic polymer (A) is not limited as long as it is a monomer having a structure constituted by combining one type of unsaturated bond arbitrarily selected from the above-mentioned various (meth)acrylic unsaturated bonds and one type of substituent arbitrarily selected from the group consisting of the above-mentioned branched alkyl group and / or branched or unbranched alkenyl group having 3 to 20 carbon atoms.

[0026] The acrylic polymer (A) used in the present invention may be a homopolymer of one monomer selected from the group of (meth)acrylic monomers as raw materials, or may be a copolymer of two or more monomers selected from the group, or a copolymer of one or more monomers selected from the group and another monomer (not included in the group). When the acrylic polymer (A) is a copolymer, the content of one or more monomers selected from the group is preferably 30 mol% or more, more preferably 50 mol% or more, and particularly preferably 80 mol% or more. If the content of one or more monomers selected from the group is 30 mol% or more, the Tg of the acrylic polymer (A) can be easily adjusted within a predetermined range (-85°C to 40°C), and adhesion to a resin substrate that is difficult to adhere to can be imparted.

[0027] The functional group (R1) of the acrylic polymer (A1) and the functional group (R2) of the acrylic polymer (A2) may be brought in from the respective raw material monomers, or may be introduced via a monomer having the functional group (R1) or (R2) after the synthesis of the acrylic polymer (A). The content of these may be calculated based on the raw material monomers, and the content of the monomer having the functional group (R1) or the functional group (R2) may be 20 mol% or less, preferably 10 mol% or less, and more preferably 5 mol% or less, based on the total raw material monomers. If the content of the monomer having the functional group (R1) or the functional group (R2) exceeds 20 mol%, the stability over time of the coating composition of this embodiment may decrease. In addition, the functional group (R1) or the functional group (R2) may remain unreacted in the obtained coating layer, and as a result, the physical properties of the coating layer, various laminates, molded products, etc. may change over time.

[0028] The total content of the (meth)acryloyl group and the unsaturated alicyclic hydrocarbon group in the side chain of the acrylic polymer (A3) is 20 mol % or less, preferably 10 mol % or less, and more preferably 5 mol % or less, based on the total amount of the raw material monomers. If the total content of the (meth)acryloyl group and the unsaturated alicyclic hydrocarbon group in the side chain of A3 exceeds 20 mol %, the stability over time of the coating composition of the present embodiment may decrease, and the crosslink density of the obtained coating layer may be too high, resulting in a decrease in its flexibility, and the adhesion to poorly adherent resin substrates and bending resistance may not be satisfactory.

[0029] The molecular weight of the acrylic polymer (A) used in the present invention is 100,000 to 6 million on a weight average basis. Also, it is preferably 300,000 to 6 million, more preferably 600,000 to 6 million. If the weight average molecular weight of the acrylic polymer (A) is 100,000 or more, the resulting coating composition and the coating layer formed from the composition have excellent adhesion to substrates such as polyester-based, polycarbonate-based, and other general-purpose resin substrates, as well as to substrates such as fluororesin-based and polyimide-based films and sheets that are difficult to adhere to, and at the same time, have strong adhesion (also referred to as adhesion) between the coating layer and the substrate, and can provide sufficient flexibility and bending resistance. Also, as the molecular weight of the acrylic polymer (A) increases, when it is used as an adhesive coating layer, it is preferable because the contamination resistance, which is essential for rework work, increases. It is considered that the higher the weight average molecular weight of the acrylic polymer (A), the better, but it is currently difficult to synthesize an acrylic polymer (A) with a molecular weight exceeding 6 million.

[0030] The Tg of the acrylic polymer (A) used in the present invention is -85°C to 40°C. Also, it is preferably -80°C to 25°C, more preferably -70°C to 10°C. When the Tg is within the range of -85°C to 40°C, the resulting coating composition can be easily applied uniformly to a film or sheet-like substrate, and a coating layer formed from the composition can easily adhere to the substrate. As the Tg of the acrylic polymer (A) decreases, the adhesion to substrates such as fluororesin-based and polyimide-based films and sheets that are difficult to adhere to tends to improve.

[0031] When the acrylic polymer (A) is a copolymer, its glass transition temperature (Tg) is a value calculated based on the following known Fox equation. When the copolymer is composed of n types of monomer components, namely, monomer 1, monomer 2, ..., monomer n, 1 / Tg=W1 / Tg1+W2 / Tg2+···+Wi / Tgi (In the formula, Tg is the glass transition temperature (unit: K) of the copolymer, Tgi (i = 1, 2, ... n) is the glass transition temperature (unit: K) when monomer i forms a homopolymer, and Wi (i = 1, 2, ... n) is the weight (mass) fraction of monomer i in all monomer components.) In this specification, the term "glass transition temperature when a homopolymer is formed" means the glass transition temperature of a homopolymer of the monomer.

[0032] The polymerizable compound (B) used in the present invention contains a monofunctional acrylic monomer (b1) having one and only one unsaturated bond in one molecule and a polyfunctional acrylic monomer (b2) having one or more and two or more unsaturated bonds in one molecule. The unsaturated bonds possessed by the monofunctional acrylic monomer (b1) and the polyfunctional acrylic monomer (b2) are one or more types selected from a methacrylate group, an acrylate group, a methacrylamide group, and an acrylamide group.

[0033] The monofunctional acrylic monomer (b1) preferably contains a monofunctional acrylic monomer having a homopolymer glass transition temperature (Tg) of 10 ° C. or less and a monofunctional acrylic monomer having a homopolymer glass transition temperature (Tg) of more than 60 ° C. By combining a monofunctional acrylic monomer having a homopolymer Tg of 10 ° C. or less and a monofunctional acrylic monomer having a homopolymer Tg of more than 60 ° C., the Tg of the acrylic polymer (A) can be easily adjusted within a predetermined range, the transparency of the coating composition containing the acrylic polymer (A) and the curability by active energy rays such as heat and light are easily improved, the surface hardness (rigidity) and bending resistance (flexibility) of the obtained coating layer are more easily compatible, and the balance between the adhesion to a poorly adherent substrate of the non-adhesive coating layer and the tack resistance and surface hardness is more easily adjusted, and the balance between the adhesion to a poorly adherent substrate of the adhesive coating layer, the adhesion, and the contamination resistance (reworkability) is more easily adjusted.

[0034] Examples of monofunctional acrylic monomers having a homopolymer Tg of 10° C. or less include methoxydipropylene glycol acrylate (Tg=−44° C.), methoxytriethylene glycol acrylate (Tg=−50° C.), methoxypolyethylene glycol acrylate (average molecular weight of polyethylene glycol: 400) (Tg=−71° C.), methoxytripropylene glycol acrylate (Tg=−75° C.), phenoxyethyl acrylate (Tg=−22° C.), methyl acrylate (Tg=8° C.), ethyl acrylate (Tg=−22° C.), butyl acrylate (Tg=−54° C.), 2-ethylhexyl acrylate (Tg=−85° C.), octyl acrylate (Tg=−65° C.), nonyl acrylate (Tg=−58° C.), dodecyl acrylate (Tg=−3° C.), isodecyl acrylate (Tg=−62° C.), and isostearyl acrylate (Tg=−18° C.). ), tridecyl acrylate (Tg=-75°C), 2-ethylhexyl methacrylate (Tg=-10°C), octyl methacrylate (Tg=-20°C), dodecyl methacrylate (Tg=-65°C), 2-hydroxyethyl acrylate (Tg=-15°C), 2-hydroxypropyl acrylate (Tg=-7°C), 4-hydroxybutyl acrylate (Tg=-40°C), methoxyethyl acrylate (Tg=-50°C), ethoxyethyl acrylate (Tg=-50°C), Examples of such monofunctional acrylic monomers include methoxyethyl acrylate (Tg = -50°C), methoxybutyl acrylate (Tg = -56°C), 3-methoxypropyl acrylate (Tg = -75°C), butoxyethyl acrylate (Tg = -40°C), phenoxydiethylene glycol acrylate (Tg = -25°C), dicyclopentenyloxyethyl acrylate (Tg = 10°C), and tetrahydrofurfuryl acrylate (Tg = -12°C). These monofunctional acrylic monomers having a homopolymer Tg of 10°C or less may be used alone or in combination of two or more.

[0035] Examples of monofunctional acrylic monomers having a homopolymer Tg of more than 60° C. include isobornyl acrylate (Tg=94° C.), cyclohexyl methacrylate (Tg=66° C.), 2-hydroxyethyl methacrylate (Tg=71° C.), 4-t-butylcyclohexyl acrylate (Tg=81° C.), dicyclopentenyl acrylate (Tg=120° C.), dicyclopentanyl acrylate (Tg=120° C.), acryloylmorpholine (Tg=145° C.), N,N-dimethylacrylamide (Tg=119° C.), and N,N-diethyl Examples of such monomers include acrylamide (Tg=81°C), N-(2-hydroxyethyl)acrylamide (Tg=98°C), N-isopropylacrylamide (Tg=134°C), acrylamide (Tg=153°C), methacrylamide (Tg=77°C), diacetoneacrylamide (Tg=77°C), N-methylacrylamide (Tg=130°C), N-methylmethacrylamide (Tg=65°C), N-ethylacrylamide (Tg=100°C), N-octylacrylamide (Tg=79°C), and acrylic acid (Tg=106°C). These monofunctional acrylic monomers having homopolymer Tg exceeding 60°C may be used alone or in combination of two or more.

[0036] Examples of the polyfunctional acrylic monomer (b2) include alkylene glycol di(meth)acrylates, polyalkylene glycol di(meth)acrylates, polyester di(meth)acrylates, polycarbonate di(meth)acrylates, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta ... Examples of the polyfunctional acrylic monomer (b2) include erythritol hexa(meth)acrylate, tri(meth)acryloyloxyethoxytrimethylolpropane, glycerin polyglycidyl ether poly(meth)acrylate, isocyanuric acid ethylene oxide modified tri(meth)acrylate, ethylene oxide modified dipentaerythritol penta(meth)acrylate, ethylene oxide modified dipentaerythritol hexa(meth)acrylate, ethylene oxide modified pentaerythritol tri(meth)acrylate, ethylene oxide modified pentaerythritol tetra(meth)acrylate, succinic acid modified pentaerythritol tri(meth)acrylate, etc. These polyfunctional acrylic monomers (b2) may be used alone or in combination of two or more.

[0037] The coating composition of this embodiment contains 0.5 to 30.0% by mass of an acrylic polymer (A) and 70.0 to 99.5% by mass of a polymerizable compound (B). If the contents of the acrylic polymer (A) and the polymerizable compound (B) are within these ranges, the resulting coating composition and the coating layer formed from the coating composition have good adhesion to substrates such as film-shaped and sheet-shaped substrates, and can be suitably used for various applications. In addition, although it depends on the molecular weight of the acrylic polymer (A), when the acrylic polymer (A) is contained in an amount of 0.5% by mass or more, even if a coating layer having a crosslinked structure is produced from the coating composition by various polymerization reactions, the adhesion to the substrate is good, and the curing shrinkage is low, so that the formed coating layer is not easily peeled off from the substrate and has high flex resistance. From the viewpoint of further improving the surface hardness and scratch resistance of the obtained non-adhesive coating layer and laminate, the coating composition preferably contains 0.5 to 25.0 mass% of acrylic polymer (A) and 75.0 to 99.5 mass% of polymerizable compound (B), and more preferably contains 1.0 to 20.0 mass% of acrylic polymer (A) and 80.0 to 99.0 mass% of polymerizable compound (B). From the viewpoint of further improving the stain resistance and step conformability of the obtained adhesive coating layer and laminate, the coating composition preferably contains 1.0 to 30.0 mass% of acrylic polymer (A) and 70.0 to 99.0 mass% of polymerizable compound (B), and more preferably contains 2.0 to 25.0 mass% of acrylic polymer (A) and 75.0 to 98.0 mass% of polymerizable compound (B).

[0038] The polymerizable compound (B) contains a monofunctional acrylic monomer (b1) and a polyfunctional acrylic monomer (b2). The content of the monofunctional acrylic monomer (b1) is preferably 10.0 to 95.0% by mass based on the total amount of the coating composition (D). The monofunctional acrylic monomer (b1) has an effect of improving the compatibility between the acrylic polymer (A) and the polyfunctional acrylic monomer (b2). If the content is 10.0% by mass or more, the transparency of the coating composition (D) and the transparency and yellowing resistance of the coating layer after curing are good. If the content of the monofunctional acrylic monomer (b1) is 95.0% by mass or less, the contents of the acrylic polymer (A) and the polyfunctional acrylic monomer (b2) in the coating composition (D) can be easily adjusted. If the content of the polyfunctional acrylic monomer (b2) is 80.0% by mass or less, the contents of the acrylic polymer (A) and the monofunctional acrylic monomer (b1) in the coating composition (D) can be easily adjusted according to the purpose, and the curing shrinkage resistance and bending resistance of the resulting coating layer are good, which is preferable.

[0039] In the coating composition used for the non-tacky coating layer and laminate, the content of the monofunctional acrylic monomer (b1) is preferably 15.0 to 80.0 mass%, and particularly preferably 20.0 to 60.0 mass%, from the viewpoint of further improving the adhesion and bending resistance of the obtained non-tacky coating layer and laminate. In addition, the content of the polyfunctional acrylic monomer (b2) is preferably 2.0 to 80.0 mass%, more preferably 5.0 to 60.0 mass%, and particularly preferably 10.0 to 50.0 mass%, from the viewpoint of quickly curing the coating composition (D) and sufficiently satisfying the rigidity properties such as surface hardness, tack resistance, and scratch resistance of the obtained coating layer.

[0040] In the coating composition used for the adhesive coating layer and the laminate, the content of the monofunctional acrylic monomer (b1) is more preferably 30.0 to 80.0 mass%, and particularly preferably 45.0 to 70.0 mass%, from the viewpoint of further improving the wettability and adhesiveness to the substrate. In addition, the content of the polyfunctional acrylic monomer (b2) is more preferably 0.5 to 20.0 mass%, and particularly preferably 0.5 to 10.0 mass%, from the viewpoint of improving the stain resistance and moist heat resistance of the resulting adhesive coating layer and maintaining good adhesiveness. Furthermore, the content of the polyfunctional acrylic monomer (b2) is most preferably 1.0 to 5.0 mass% or less, from the viewpoint of fully satisfying the adhesion to the poorly adhesive substrate and the step conformability.

[0041] The polymerizable compound (B) may further contain a urethane oligomer (b3) other than the monofunctional acrylic monomer (b1) and the polyfunctional acrylic monomer (b2). The urethane oligomer (b3) is a polyfunctional urethane oligomer having one or more and two or more unsaturated bonds in one molecule and having a urethane bond. The unsaturated bonds of the urethane oligomer (b3) are one or more selected from a methacrylate group, an acrylate group, a methacrylamide group, and an acrylamide group. In addition, when the urethane oligomer (b3) has one or more methacrylamide groups or acrylamide groups as unsaturated bonds in the molecule, that is, when the urethane oligomer (b3) is a urethane (meth)acrylamide oligomer, the curability of the coating composition (D) is improved, and at the same time, the curing shrinkage when the coating composition (D) is cured by various polymerization methods is low, and a coating layer having sufficient shrinkage resistance can be obtained, which is preferable.

[0042] The urethane oligomer (b3) can be obtained by a known urethane reaction method using a polyol, a polyisocyanate, and a (meth)acrylate having a hydroxyl group and / or a (meth)acrylamide having a hydroxyl group. The urethane oligomer (b3) has one or more polyol-derived skeletons selected from an ether skeleton, an ester skeleton, a carbonate skeleton, a silicone skeleton, an olefin skeleton, and an acrylic skeleton, and the number of unsaturated bonds in one molecule is preferably 2 or more from the viewpoint of improving the curability of the coating composition (D), and is usually 10 or less, preferably 6 or less, and more preferably 4 or less from the viewpoint of achieving both the rigidity and flexibility of the resulting coating layer.

[0043] The average molecular weight (Mw) of the urethane oligomer (b3) is preferably 1,500 to 100,000, and more preferably 2,000 to 50,000. When the average molecular weight (Mw) of the urethane oligomer (b3) is within this range, the coating composition (D) has good wettability and adhesion to various substrates, the resulting coating layer has high adhesion to a wide range of substrates, from general-purpose resin substrates to substrates with poor adhesion, and laminates, molded articles, and the like formed from such a coating layer have sufficient flex resistance and moist heat resistance.

[0044] The content of the urethane oligomer (b3) is preferably 2.0 to 50.0% by mass based on the total amount of the coating composition (D). When the content of (b3) is 2.0% by mass or more, the curability of the coating composition is improved, and the compatibility between the rigidity and flexibility of the resulting coating layer is improved. On the other hand, when the content of (b3) exceeds 50.0% by mass, the wet heat resistance of the cured coating layer, the intended laminate, and the molded product may decrease. When used in a non-adhesive coating layer and laminate, the content of (b3) is more preferably 2.0 to 35.0% by mass, and particularly preferably 5.0 to 20.0% by mass, from the viewpoint of further improving the adhesion and bending resistance. When used in an adhesive coating layer and laminate, the content of (b3) is more preferably 5.0 to 50.0% by mass, and particularly preferably 10.0 to 30.0% by mass, from the viewpoint of further improving the adhesion (adhesive strength) and contamination resistance.

[0045] The coating composition (D) can be polymerized by thermal polymerization, photopolymerization, or hybrid polymerization. In the case of thermal polymerization, it is preferable to use a thermal polymerization initiator. In the case of polymerization (photopolymerization) by active energy rays such as light, when an electron beam is used as the active energy ray, it is not necessary to use a photopolymerization initiator, but when ultraviolet rays, visible rays, or the like are used, it is preferable to use a photopolymerization initiator. In the case of hybrid polymerization, a thermal polymerization initiator and a photopolymerization initiator may be used in combination. When (A1) having an active hydrogen-containing functional group (R1) and (A2) having a functional group (R2) in the side chain that reacts with the active hydrogen-containing functional group (R1) are used, the polymerizable compound (B) may be polymerized by a photopolymerization initiator, and then the reaction by the functional groups R1 and R2 may be carried out by heating. When (A3) having a (meth)acryloyl group or an unsaturated alicyclic hydrocarbon group in the side chain is used, it may be copolymerized with the polymerizable compound (B) by a photopolymerization initiator, or after the polymerizable compound (B) is photopolymerized, (A3) may be polymerized by a thermal polymerization initiator.

[0046] The thermal polymerization initiator may be appropriately selected from commonly used initiators such as azo initiators, peroxide initiators, persulfate initiators, and redox initiators. For example, examples of azo initiators include VA-044, VA-46B, V-50, VA-057, VA-061, VA-067, VA-086, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (VAZO 33), 2,2'-azobis(2-amidinopropane) dihydrochloride (VAZO 50), 2,2'-azobis(isobutyronitrile) (VAZO 64), 2,2'-azobis-2-methylbutyronitrile (VAZO 67), and 1,1-azobis(1-cyclohexanecarbonitrile) (VAZO 88) (all manufactured by DuPont). Examples of suitable azobis(2,4-dimethylvaleronitrile) include 2,2'-azobis(2-cyclopropylpropionitrile) (V-601) and 2,2'-azobis(2,4-dimethylvaleronitrile) (V-65) (available from Wako Pure Chemical Industries, Ltd.). Examples of peroxide initiators include benzoyl peroxide, acetyl peroxide, lauroyl peroxide, decanoyl peroxide, dicetyl peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate (Perkadox 16S) (available from Akzo Nobel), di(2-ethylhexyl)peroxydicarbonate, t-butyl peroxypivalate (Lupersol 11) (available from Elf Atochem), t-butyl peroxy-2-ethylhexanoate (Trigonox21-C50) (available from Akzo Nobel), dicumyl peroxide, etc. Examples of persulfate initiators include potassium persulfate, sodium persulfate, ammonium persulfate, etc. Redox (oxidation-reduction) initiators include, for example, combinations of the persulfate initiators with reducing agents such as sodium metabisulfite and sodium bisulfite, systems based on the organic peroxides and tertiary amines (e.g., a system based on benzoyl peroxide and dimethylaniline), systems based on organic hydroperoxides and transition metals (e.g., a system based on cumene hydroperoxide and cobalt naphthate), and the like.These thermal polymerization initiators can be used alone or in combination of two or more.

[0047] The content of the thermal polymerization initiator is preferably from 0.1 to 10% by mass, more preferably from 0.5 to 5% by mass, and particularly preferably from 1.0 to 3% by mass, based on the total amount of the coating composition (D).

[0048] The photopolymerization initiator may be appropriately selected from commonly used ones such as acetophenone type, benzoin type, benzophenone type, α-aminoketone type, xanthone type, anthraquinone type, acylphosphine oxide type, and polymeric photopolymerization initiator type. For example, acetophenones include diethoxyacetophenone, 2,2-dimethoxy-1,2-diphenylethan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)-phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexylphenylketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1, benzoins include benzoin, α-methylbenzoin, α-phenylbenzoin, α-allylbenzoin, α-benzoylbenzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzyl dimethyl ketal, benzophenones include benzophenone, benzoylbenzoic acid, benzoylbenzoic acid, Methyl aldehyde, α-aminoketones such as 2-methyl-1-(4-methylthiophenyl)-2-(4-morpholinyl)-1-propanone, 2-benzyl-2-(dimethylamino)-1-(4-(4-morpholinyl)phenyl)-1-butanone, 2-(dimethylamino)-2-(4-methylphenyl)methyl-1-(4-(4-morpholinyl)phenyl)-1-butanone, xanthones such as xanthone, thioxanthone, and anthraquinones. Examples of the photopolymerization initiator include anthraquinone, 2-methylanthraquinone, and 2-ethylanthraquinone; examples of the acylphosphine oxides include bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide; and examples of the polymer photopolymerization initiator include a polymer of 2-hydroxy-2-methyl-1-(4-(1-methylvinyl)phenyl)propan-1-one. These photopolymerization initiators can be used alone or in combination of two or more.

[0049] The content of the photopolymerization initiator is preferably from 0.01 to 10% by mass, more preferably from 0.1 to 5% by mass, and particularly preferably from 0.5 to 3% by mass, based on the total amount of the coating composition (D).

[0050] The coating composition (D) may not contain a solvent, but may contain a solvent or various additives as necessary. The solvent is not particularly limited as long as it can be mixed with the coating composition (D) to obtain a transparent and uniform solution and does not react with each component of the coating composition (D). Examples of the solvent include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, heptane, octane, decane, and cyclohexane, esters such as ethyl acetate, butyl acetate, and 2-hydroxyethyl acetate, aliphatic alcohols such as ethyl alcohol, n-propyl alcohol, and isopropyl alcohol, glycols such as ethylene glycol, propylene glycol, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate, ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, 3-methoxy-N,N-dimethylpropanamide, and 3-butoxy-N,N-dimethylpropanamide, and acetonitrile. These solvents may be used alone or in combination of two or more. From the viewpoint of applying the coating composition (D) to a substrate and then removing the solvent before carrying out polymerization or curing, it is preferable to use ethyl acetate, methyl ethyl ketone, acetone, or the like which has a low boiling point and is easy to remove.

[0051] The coating composition (D) may contain various additives as necessary. Specifically, the additives may include thermal polymerization inhibitors, antioxidants, ultraviolet sensitizers, preservatives, phosphate esters and other flame retardants, surfactants, antistatic agents, colorants such as pigments and dyes, fragrances, defoamers, fillers, silane cupping agents, surface tension regulators, plasticizers, surface lubricants, leveling agents, softeners, organic fillers, inorganic fillers, silica particles, etc. The amount of these other components added is not particularly limited as long as it does not adversely affect the properties of the coating composition (D), and is preferably 5% by mass or less based on the entire coating composition (D).

[0052] The third embodiment of the present invention is a laminate having a coating layer formed by applying the coating composition (D) to various substrates and curing the coating composition (D) by various polymerization methods, a surface protection sheet such as a cover film, and a molded product such as a substrate. The film used as the substrate is any one of films selected from polyester film, polycarbonate film, fluororesin film, polyimide film, triacetyl cellulose film, acrylic film, polystyrene film, polyvinyl chloride film, polyvinyl alcohol film, and nylon film. The film of the transparent substrate is any one of films selected from transparent polyester film, transparent polycarbonate film, transparent fluororesin film, transparent polyimide film, transparent triacetyl cellulose film, transparent acrylic film, transparent polystyrene film, transparent polyvinyl chloride film, transparent polyvinyl alcohol film, and transparent nylon film, and has a total light transmittance of 80% or more. The coating composition (D) is applied to one or both sides of various substrate films, and polymerized and cured by various polymerization methods to obtain a laminate having a coating layer on one or both sides of the substrate. The coating composition (D) can be applied by a conventional method, for example, a typical coating film forming method such as spin coating, spray coating, knife coating, dipping, gravure roll, reverse roll, screen printing, or bar coater. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following, "parts" and "%" are all by mass unless otherwise specified.

[0054] The abbreviations of the acrylic polymer (A), polymerizable compound (B), initiator (C) and various substrates (E) described in the examples and comparative examples are as follows. <Acrylic polymer (A)> A-1: Homopolymer of 2-ethylhexyl acrylate (b1-3), weight average molecular weight (Mw) is 5.6 million, Tg = -85°C A-2: 2-ethylhexyl acrylate (b1-3), butyl acrylate (b1-4) and N,N-dimethylacrylamide (b1-8) copolymer (molar ratio = 70 / 10 / 20), Mw = 2.2 million, Tg = -69°C A-3: Copolymer of butyl acrylate (b1-4) and N-isopropylacrylamide (b1-14) (molar ratio = 70 / 30), Mw = 600,000, Tg = -22°C A-4: Ethyl acrylate (Tg = -20°C), copolymer of isobutyl methacrylate (b1-1) and diacetone acrylamide (b1-13) (molar ratio = 30 / 50 / 20), Mw = 120,000, Tg = 35°C A-5: Copolymer of 2-ethylhexyl acrylate (b1-3) and oleyl acrylamide (b1-16) (molar ratio = 80 / 20), Mw = 900,000, Tg = -60°C A-6: Copolymer of 2-ethylhexyl acrylate (b1-3) and allyl methacrylate (Tg = 52 ° C) (molar ratio = 90 / 10), Mw = 850,000, Tg = -79 ° C A1-1: 2-ethylhexyl acrylate (b1-3), copolymer of N,N-diethylacrylamide (b1-9) and N-(2-hydroxyethyl)acrylamide (b1-10) (molar ratio = 60 / 35 / 5), Mw = 1.1 million, Tg = -52°C A1-2: Copolymer of isobutyl acrylate (Tg -26°C) and acrylic acid (b1-17) (molar ratio = 95 / 5), Mw = 2.8 million, Tg = -24°C A2-1: copolymer of isodecyl acrylate (b1-5), isobornyl acrylate (b1-11) and glycidyl methacrylate (b1-19) (molar ratio = 70 / 28 / 2), Mw = 330,000, Tg = -29°C A2-2: 2-ethylhexyl acrylate (b1-3), acryloylmorpholine (b1-12), 2-isocyanatoethyl methacrylate (b1-18) (molar ratio = 80 / 17 / 3), Mw = 730,000, Tg = -67°C A3-1: A copolymer of isodecyl acrylate (b1-5), acryloylmorpholine (b1-12) and acrylic acid (b1-17) (molar ratio = 50 / 10 / 20) to which glycidyl methacrylate (molar ratio = 20) has been added, Mw = 180,000, Tg = 22°C A3-2: 2-ethylhexyl acrylate (b1-3), oleyl acrylamide (b1-16), isobornyl acrylate (b1-11) and N-acryloyloxyethyl norbornene carboxamide (registered trademark "Kohshylmer" manufactured by KJ Chemicals Co., Ltd.) copolymer (molar ratio = 25 / 25 / 40 / 10), Mw = 240,000, Tg = 8°C <Polymerizable compound (B)> b1-1: Isobutyl methacrylate (Tg=48°C) b1-2: Cyclohexyl acrylate (Tg=15℃) b1-3: 2-ethylhexyl acrylate (Tg=-85℃) b1-4: Butyl acrylate (Tg = -54°C) b1-5: Isodecyl acrylate (Tg=-62℃) b1-6: Phenoxyethyl acrylate (Tg=-22℃) b1-7: Dicyclopentenyloxyethyl acrylate (Tg = 10°C) b1-8: N,N-dimethylacrylamide (Tg = 119 ° C.) (registered trademark "Kohshylmer", "DMAA" manufactured by KJ Chemicals Co., Ltd.) b1-9: N,N-diethylacrylamide (Tg = 81 ° C.) (registered trademark "Kohshylmer", "DEAA" manufactured by KJ Chemicals Co., Ltd.) b1-10: N-(2-hydroxyethyl)acrylamide (Tg = 98°C) (registered trademark "Kohshylmer", "HEAA", manufactured by KJ Chemicals Co., Ltd.) b1-11: Isobornyl acrylate (Tg = 94°C) b1-12: Acryloylmorpholine (Tg = 145°C) (registered trademark "Kohshylmer", "ACMO", manufactured by KJ Chemicals Co., Ltd.) b1-13: Diacetone acrylamide (Tg = 77°C) (registered trademark "Kohshylmer" manufactured by KJ Chemicals Co., Ltd.) b1-14: N-isopropylacrylamide (Tg = 134 ° C.) (registered trademark "Kohshylmer", "NIPAM" manufactured by KJ Chemicals Co., Ltd.) b1-15: 4-tert-butylcyclohexyl acrylate (Tg = 77°C) (registered trademark "Kohshylmer" manufactured by KJ Chemicals Co., Ltd.) b1-16: Oleyl acrylamide (Tg = 29°C) (registered trademark "Kohshylmer" manufactured by KJ Chemicals Co., Ltd.) b1-17: Acrylic acid (Tg=106℃) b1-18: 2-isocyanatoethyl methacrylate (Tg = 60°C) (Kalends MOI, manufactured by Showa Denko K.K.) b1-19: Glycidyl methacrylate (Tg=46℃) b2-1: Pentaerythritol (tri / tetra)acrylate (3-4 functional) B2-2: Dipentaerythritol hexaacrylate (6 functional groups) b2-3: Bisphenol A ethylene glycol (4) adduct diacrylate (bifunctional, Light Acrylate BP-4EAL, Kyoeisha Chemical Co., Ltd.) B2-4: Tripropylene glycol diacrylate (2 functional) b3-1: Polyester-based urethane acrylate (bifunctional, UV-3000B, molecular weight Mw=18000, manufactured by Mitsubishi Chemical Corporation) b3-2: Polyether-based urethane acrylate (bifunctional, UV-6640B, molecular weight Mw=5000, manufactured by Mitsubishi Chemical Corporation) b3-3: Polycarbonate-based urethane acrylamide (registered trademark "Quick Cure", bifunctional, molecular weight Mw = 15000, manufactured by KJ Chemicals Co., Ltd.) b3-4: Polyester-based urethane acrylamide (registered trademark "Quick Cure", trifunctional, molecular weight Mw=9000, manufactured by KJ Chemicals Co., Ltd.) b3-5: Polyether-based urethane acrylamide (registered trademark "Quick Cure", bifunctional, molecular weight Mw = 35000, manufactured by KJ Chemicals Co., Ltd.) <Initiator (C)> C-1: 1-Hydroxycyclohexyl phenyl ketone (photopolymerization initiator Omnirad 184, manufactured by IGM Resins B.V.) C-2: 2-hydroxy-2-methyl-1-phenyl-propan-1-one (photopolymerization initiator Omnirad 1173, manufactured by IGM Resins B.V.) C-3: 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (photopolymerization initiator Omnirad TPO, manufactured by IGM Resins B.V.) C-4: 2,2'-azobis(2,4-dimethylvaleronitrile) (thermal polymerization initiator V-65) (manufactured by Wako Pure Chemical Industries, Ltd.) <Film-like substrate> E-1: Polyethylene terephthalate (PET) film (Cosmoshine A4300, one-sided anchor coat treatment, manufactured by Toyobo Co., Ltd.) E-2: Polycarbonate film (Panlite PC-2151, manufactured by Teijin Ltd.) E-3: Polyimide film (Kapton, manufactured by Toray DuPont) E-4: Transparent polyimide film (TORMENDTM, manufactured by IST) E-5: Transparent acrylic film (Sunduren SD-014, manufactured by Kaneka Corporation)

[0055] Examples 1 to 24 and Comparative Examples 1 to 8 The acrylic polymer (A), the polymerizable compound (B), the initiator (C), etc. were added to a container in the predetermined parts by mass shown in Tables 1 to 3 and mixed uniformly to prepare the coating compositions (D-1) to (D-24) of Examples 1 to 24 and the mixed solutions (F-1) to (F-8) of Comparative Examples 1 to 8. Then, using the obtained coating compositions of the Examples and the mixed solutions of the Comparative Examples, a non-adhesive coating layer and an adhesive coating layer (adhesive layer) were produced as a cured film by heating and / or ultraviolet (UV) irradiation, and a film laminate having these coating layers was produced and evaluated by the following method. The polymer used in Comparative Example 3 was a homopolymer (P-1, molecular weight Mw = 100,000, Tg = -54 ° C.) of butyl acrylate (b1-4), and the polymer used in Comparative Example 7 was a copolymer (P-2, molar ratio = 90 / 10, molecular weight Mw = 150,000, Tg = -44 ° C.) of butyl acrylate (b1-4) and acrylic acid (b1-17).

[0056] [Table 1]

[0057] [Table 2]

[0058] [Table 3]

[0059] <Non-adhesive coating layer production and evaluation> In Examples 25 to 40, the prepared coating compositions (D-1) to (D-16) were used, and in Comparative Examples 9 to 12, the prepared mixed solutions (F-1) to (F-4) were used. Using a tabletop coater (Coater TC-1, manufactured by Mitsui Electric Seiki Co., Ltd.), coating was performed with a bar coater (RDS #6) on the anchor coat surface of a 100 μm thick polyethylene terephthalate (PET) film ("Cosmoshine A4100", manufactured by Toyobo Co., Ltd., one side anchor coat treatment) to a film thickness of 10 μm to obtain an uncured coating film. In Example 25 and Comparative Example 9, the uncured coating film was aged in a thermostatic chamber at 80° C. for 5 hours to obtain a coating layer as a cured film. In Examples 26 to 40 and Comparative Examples 10 to 12, the uncured coating film was used and ultraviolet light (illuminance 700 mW / cm 2 , cumulative light intensity 1000mJ / cm 2 ) (apparatus: inverter type conveyor ECS-4011GX manufactured by iGraphics, metal halide lamp: M04-L41 manufactured by iGraphics) was used to obtain a coating layer as a cured film. In the case of Examples 31 to 34 and 39 using coating compositions (D-7) to (D-10) and (D-15) using (A1) having an active hydrogen-containing functional group (R1) in the side chain as the acrylic polymer (A) or (A2) having a functional group (R2) that reacts with the active hydrogen-containing functional group (R1) in the side chain, after the ultraviolet irradiation, aging was further performed for 3 days in a thermostatic chamber at 40 ° C. to obtain a coating layer for evaluation. The curability of the obtained coating composition, the surface hardness, tack resistance, scratch resistance, shrinkage resistance and moist heat resistance of the non-adhesive coating layer were measured according to the following methods. The evaluation results are shown in Table 4.

[0060] <Curability of Coating Composition (D) and Mixture (F)> The peak derived from the vinyl group of the coating composition (1620 to 1640 cm -1 The height of the cured layer was measured by FT-IR, and the curing rate was calculated as follows to evaluate the curability of the coating composition. Curing rate (%)=(height of peak derived from vinyl groups before curing−height of peak derived from vinyl groups after curing) / height of peak derived from vinyl groups before curing×100%). ◎: Curing rate 90% or more ○: Cure rate 80% or more but less than 90% ×: Curing rate less than 80%

[0061] <Shrinkage resistance of non-adhesive coating layer> A cured non-adhesive coating layer was prepared in the same manner as described above, except that the thickness of the non-adhesive coating layer was set to 50 μm. The cured coating layer thus obtained was cut into a 10×10 cm 2 The height of the raised corners was measured, and the average value was calculated from the measurements of five pieces cut in the same manner. ◎: The floating height is less than 0.5 mm. ○: The floating height is 0.5 mm or more and less than 1 mm. ×: The floating height is 1 mm or more.

[0062] <Tack resistance of non-adhesive coating layer> A cured non-adhesive coating layer having a thickness of 10 μm was prepared in the same manner as above. The surface of the coating layer was touched with a finger, and the tackiness of the non-adhesive coating layer was evaluated based on the degree of stickiness. ◎: Not sticky at all. ○: There is some stickiness, but finger marks do not remain on the surface. △: Sticky and leaves finger marks on the surface. ×: Very sticky, fingers stick to the surface.

[0063] <Scratch resistance of non-adhesive coating layer> A hardened non-adhesive coating layer having a thickness of 10 μm was prepared in the same manner as above, and then coated with #0000 steel wool at 100 g / cm 2 The sample was then reciprocated 10 times while applying a load of 1000 mm, and the occurrence of scratches was visually evaluated. ⊚: Almost no peeling or damage to the film was observed. ○: Slight fine scratches are observed in some parts of the film. △: Streaky scratches are observed over the entire surface of the film. ×: Peeling of the film occurs.

[0064] <Surface hardness of non-adhesive coating layer> A hardened non-adhesive coating layer having a thickness of 10 μm was prepared in the same manner as described above, and when the layer was scratched with a pencil at an angle of 45° for approximately 10 mm in accordance with JIS K 5600-5-4, the pencil hardness was determined as the hardest pencil that did not scratch the surface of the non-adhesive coating layer. ◎: Pencil hardness is 3H or higher ○:Pencil hardness H~2H △: Pencil hardness is B~F ×: Pencil hardness is 2B or less

[0065] <Moisture and heat resistance of non-adhesive coating layer> A cured non-adhesive coating layer having a thickness of 10 μm was prepared in the same manner as above, and was maintained for 100 hours under conditions of a temperature of 85° C. and a relative humidity of 85%, after which the occurrence of bubbles or cloudiness was visually observed and evaluated as follows. ◎: Transparent and no air bubbles. ○: There is very little cloudiness, but no bubbles are generated. ×: Cloudiness or bubbles are generated.

[0066] <Preparation and evaluation of film laminates with non-adhesive coating layer> A non-adhesive coating layer having a thickness of 10 μm was prepared on one side of each film by the same method as above using polyethylene terephthalate (PET) film (E-1), polycarbonate (PC) film (E-2), polyimide (PI) film (E-3), transparent polyimide film (E-4), and acrylic film (E-5) as the substrate for preparing the non-adhesive coating layer. The obtained substrate film with the non-adhesive coating layer was made into various film laminates, and the adhesion between the coating layer and the substrate film, and the bending resistance and transparency of the film laminate were evaluated according to the following method. The results are shown in Table 4.

[0067] <Adhesion of film laminate having a non-adhesive coating layer> The obtained film laminate was used to make a 1×1 mm 2The surface of the coating layer was cut into 100 squares, and cellophane tape was attached to it, and then the cellophane tape was quickly peeled off. The number of squares that remained on the base film were counted and evaluated as follows. The results are shown in Table 4. ◎: 100 squares of coating layer remain ○: 90-99 squares of coating layer remain △: 60 to 89 squares of coating layer remain ×: Less than 60 squares of coating layer remain

[0068] <Flexibility of film laminate having a non-adhesive coating layer> The obtained film laminate was cut into test pieces of 15 mm wide x 100 mm long, and a bending test was carried out 20,000 times in accordance with JIS P8115 using an MIT type folding fatigue tester (Toyo Seiki Seisakusho Co., Ltd., D type) under conditions of a load of 0.25 kgf on the test pieces, a bending clamp radius R of 2.0 mm, a bending angle of 135°, and a speed of 175 cpm. After the test, the coating layer was visually observed for peeling, cracks, and cloudiness, and evaluated as follows. The results are shown in Table 4. ◎: Transparent and no peeling or cracking occurs. ◯: There is very little white turbidity, but no peeling or cracks. Δ: Slight clouding, peeling or cracks occurred. ×: Clouding, peeling or cracks occurred.

[0069] <Transparency of film laminate having a non-adhesive coating layer> The obtained film laminate was cut into 100 mm pieces. 2 The uncolored film laminate was cut into test pieces and left to stand for 24 hours in an environment at a temperature of 23°C and a relative humidity of 50%, and then the total light transmittance of the uncolored film laminate was measured under the same conditions in accordance with JIS K 7361-1 and evaluated as follows. The results are shown in Table 4. Note that since the polyimide film (E-3) was yellow, the transparency evaluation was not performed on the film laminate. ◎: Transmittance is 90% or more ○: Transmittance is 80% or more and less than 90% ×: Transmittance is less than 80%

[0070] [Table 4]

[0071] <Adhesive coating layer production and evaluation> Examples 41 to 48 and Comparative Examples 13 to 16 In Examples 41 to 48, the prepared coating compositions (D-17) to (D-24) were used, and in Comparative Examples 13 to 16, the prepared mixed solutions (F-5) to (F-8) were used. Using a tabletop coater (Coater TC-1, manufactured by Mitsui Electric Seiki Co., Ltd.), coating was performed with a bar coater (RDS 30) on the anchor coat surface of a 100 μm thick polyethylene terephthalate (PET) film ("Cosmoshine A4100" manufactured by Toyobo Co., Ltd., one side anchor coat treatment) to a film thickness of 50 μm. Thereafter, a 50 μm thick light release PET film (manufactured by Toyobo Co., Ltd., polyester film E7002) was placed on top of the coating film, and ultraviolet light (apparatus: inverter type conveyor device ECS-4011GX manufactured by I-Graphics, metal halide lamp: M04-L41 manufactured by I-Graphics, ultraviolet light (illuminance 700 mW / cm 2 , cumulative light intensity 1000mJ / cm 2 ) irradiation, and then the light release PET film was removed to obtain an adhesive coating layer as a cured film. In the case of Examples 44 to 46 and 48 using coating compositions (D-20) to (D-22) and (D-24) using (A1) having an active hydrogen-containing functional group (R1) in the side chain as the acrylic polymer (A) or (A2) having a functional group (R2) that reacts with the active hydrogen-containing functional group (R1) in the side chain as the acrylic polymer (A), after the ultraviolet irradiation, aging was further performed for 3 days in a thermostatic chamber at 40 ° C., and then the light release PET film was removed to obtain an adhesive coating layer for evaluation. The curability of the obtained coating composition, the shrinkage resistance, moist heat resistance and step followability of the adhesive coating layer were measured according to the following methods. The evaluation results are shown in Table 5.

[0072] <Curing properties of coating composition (D) and mixed liquid (F)> The peak derived from the vinyl group of the coating composition (1620 to 1640 cm -1 The height of the cured layer was measured by FT-IR, and the curing rate was calculated as follows to evaluate the curability of the coating composition. Curing rate (%)=(height of peak derived from vinyl groups before curing−height of peak derived from vinyl groups after curing) / height of peak derived from vinyl groups before curing×100%). ◎: Curing rate 90% or more ○: Cure rate 80% or more but less than 90% ×: Curing rate less than 80%

[0073] <Shrinkage resistance of adhesive coating layer> A cured adhesive coating layer was prepared in the same manner as above, except that the thickness of the adhesive coating layer was 100 μm, and a 10 × 10 cm 2 The height of the raised corners was measured, and the average value was calculated from the measurements of five pieces cut in the same manner. ◎: The floating height is less than 0.5 mm. ○: The floating height is 0.5 mm or more and less than 1 mm. ×: The floating height is 1 mm or more.

[0074] <Moisture and heat resistance of adhesive coating layer> A cured adhesive coating layer having a thickness of 50 μm was prepared in the same manner as above, and was maintained for 100 hours under conditions of a temperature of 85° C. and a relative humidity of 85%, after which the occurrence of bubbles or cloudiness was visually observed and evaluated as follows. ◎: Transparent and no air bubbles. ○: There is very little cloudiness, but no bubbles are generated. ×: Cloudiness or bubbles are generated.

[0075] <Adhesive coating layer conforms to uneven surfaces> A 20 μm thick black tape was attached to a polyimide substrate to prepare a stepped glass. The adhesive coating layer was transferred to the stepped glass, and the glass was pressed and attached by a roller with a load of 2 kg, going back and forth once (pressing speed: 300 mm / min) in an atmosphere of 23°C and 50% relative humidity. After leaving the glass at 80°C for 24 hours, the condition of the stepped portion was observed with an optical microscope and evaluated into four stages as follows. The results are shown in Table 5. ⊚: No bubbles are observed. ○: A few small spherical bubbles are visible. △: Large bubbles are observed and may be connected to each other. ×: Large bubbles are connected to each other and spread out linearly at the step portions.

[0076] <Stain resistance of adhesive coating layer> A cured adhesive coating layer with a thickness of 50 μm was prepared in the same manner as above, the light release PET film was peeled off, and the adhesive coating layer was transferred to one side of the base film (E-1) to (E-5), and pressure-applied by two round trips using a pressure roller weighing 2 kg, and left at 80 ° C. for 24 hours. After that, the films (E-1) to (E-5) were peeled off, and the state of the adhesive coating layer remaining on the film surface was visually observed, and the stain resistance was evaluated in four stages as follows. The results are shown in Table 5. ◎: No contamination. ○: There is very little contamination. △: Slight contamination. ×: Glue (adhesive) remains.

[0077] <Preparation and evaluation of film laminates with adhesive coating layers> A cured adhesive coating layer with a thickness of 50 μm was prepared in the same manner as above, the light release PET film was peeled off, and the adhesive coating layer was transferred to one side of the base film (E-1) to (E-5), and pressure-applied by two round trips using a pressure roller weighing 2 kg to obtain various film laminates. The adhesiveness (adhesive strength), transparency, and yellowing resistance of the adhesive coating layer were evaluated according to the following methods. The results are shown in Table 5.

[0078] <Adhesiveness of adhesive coating layer of film laminate> Using the film laminate that had been left in an environment of 23°C and 50% relative humidity for 30 minutes, a 180° peel test was performed between the adhesive coating layer and each film substrate at a peel speed of 5mm / sec. in accordance with JIS Z 0237:2009 to measure the peel strength and evaluate it as follows. The results are shown in Table 5. ◎:8N / cm or more ○: 4N / cm or more and less than 8N / cm △: 2N / cm or more and less than 4N / cm ×: Less than 2N / cm

[0079] <Transparency of film laminate having adhesive coating layer> The obtained film laminate was cut into 100 mm pieces. 2 The uncolored film laminate was cut into test pieces and left to stand for 24 hours in an environment at a temperature of 23°C and a relative humidity of 50%, and then the total light transmittance of the uncolored film laminate was measured under the same conditions in accordance with JIS K 7361-1 and evaluated as follows. The results are shown in Table 5. Note that since film E-3 was yellow, the transparency of the film laminate was not evaluated. ◎: Transmittance is 90% or more ○: Transmittance is 80% or more and less than 90% ×: Transmittance is less than 80%

[0080] <Yellowing resistance of film laminate having adhesive coating layer> The obtained uncolored film laminate was set in a xenon fade meter (SC-700-WA: manufactured by Suga Test Instruments Co., Ltd.) and subjected to an irradiation of 70 mW / cm 2 After irradiating the film laminate with ultraviolet light of intensity of 1000 nm for 120 hours, the discoloration of the film laminate was visually evaluated into the following four stages. The results are shown in Table 5. Note that since film E-3 was yellow, the film laminate was not evaluated for yellowing resistance. ⊚: No yellowing was observed with the naked eye. ○: Yellowing is very slight and visible. △: Yellowing is visually confirmed. ×: Obvious yellowing is visually observed.

[0081] [Table 5]

[0082] As shown in the results of the Examples and Comparative Examples, the coating composition according to the first embodiment of the present invention contains a specific acrylate polymer (A) and a polymerizable compound (B) in a specific mass ratio, and is characterized by high polymerizability and curability by active energy rays such as heat and / or light, and good wettability and adhesion to various substrates. The non-adhesive coating layer according to one of the second embodiments of the present invention formed from the coating composition exhibits high surface hardness, tack resistance, scratch resistance, shrinkage resistance, and moist heat resistance, and in the non-adhesive coating layer and various laminates comprising the non-adhesive coating layer according to one of the third embodiments of the present invention, the non-adhesive coating layer has excellent adhesion to various resin substrates, from general-purpose polyester films and polycarbonate films to poorly adherent polyimide films, and further, it is clear that the obtained film laminate has bending resistance and transparency. Moreover, the adhesive coating layer, which is another of the second embodiment of the present invention formed from the coating composition, exhibits high shrinkage resistance and moist heat resistance, and in various laminates, which are another of the third embodiment of the present invention, which are provided with the adhesive coating layer, it is clear that the adhesive coating layer has excellent adhesion and adhesion to various resin substrates, from general-purpose polyester films and polycarbonate films to poorly adherent polyimide films, and further has transparency, stain resistance, and yellowing resistance. Film laminates, cover films, and substrates having such non-adhesive coating layers can achieve both surface hardness and bending resistance, while film laminates having adhesive coating layers have excellent adhesion and adhesion to poorly adherent polyimide films, etc., and further have properties such as shrinkage resistance, moist heat resistance, and step tracking, and can be suitably used for applications to various optical and electronic devices. [Industrial Applicability]

[0083] As explained above, the coating composition of the present invention contains 0.5 to 30.0 mass% of an acrylic polymer (A) having a branched alkyl group and / or a branched or unbranched alkenyl group having 3 to 20 carbon atoms in the side chain, and 70.0 to 99.5 mass% of a polymerizable compound (B), and the desired non-adhesive or adhesive coating layer is obtained by polymerization and curing with heat and / or active energy rays such as light. The desired laminate, cover film, or substrate is obtained by providing the coating layer on one or both sides of a resin substrate, such as a film, sheet, or substrate. By using the coating composition of the present invention, a non-adhesive coating layer having excellent wettability and adhesion to a resin substrate, while having good surface hardness, tack resistance, scratch resistance, shrink resistance, bending resistance, transparency and moist heat resistance, or an adhesive coating layer having excellent adhesion as well as good shrink resistance, moist heat resistance, step conformability, contamination resistance, transparency and yellowing resistance can be obtained, and the non-adhesive coating layer can be used as various optical members such as an optical film having the non-adhesive coating layer on one side and / or both sides of the various resin substrates. In addition, the adhesive coating layer can be used to bond various optical films, and can be obtained as various laminated films. Therefore, these various optical films and the like can be suitably used as various display and touch panel members, materials for electronic devices such as liquid crystal display devices and organic electroluminescence display devices, various sensor materials, and the like.

Claims

1. Contains 0.5 to 30.0% by mass of an acrylic polymer (A) and 70.0 to 99.5% by mass of a polymerizable compound (B); the acrylic polymer (A) has a branched alkyl group and / or a branched or unbranched alkenyl group having 3 to 20 carbon atoms in a side chain, The coating composition, wherein the polymerizable compound (B) contains a (meth)acrylamide monomer and a urethane oligomer.

2. 2. The coating composition according to claim 1, wherein the acrylic polymer (A) has a weight average molecular weight of 100,000 to 6,000,000 and a glass transition temperature (Tg) of -85°C to 40°C.

3. 3. The coating composition according to claim 1, wherein the acrylic polymer (A) is (A1) further having an active hydrogen-containing functional group (R1) in a side chain, or (A2) further having a functional group (R2) reactive with the active hydrogen-containing functional group (R1) in a side chain, and / or (A3) further having a (meth)acryloyl group or an unsaturated alicyclic hydrocarbon group in a side chain.

4. The coating composition according to any one of claims 1 to 3, characterized in that the polymerizable compound (B) contains a monofunctional acrylic monomer (b1) and a polyfunctional acrylic monomer (b2), and the content of (b1) is 10.0 to 96.0 mass% based on the total amount of the coating composition, and the content of (b2) is 0 to 80.0 mass% based on the total amount of the coating composition.

5. A coating composition described in any one of claims 1 to 4, characterized in that the content of the urethane oligomer (b3) (excluding b1 and b2) is 2.0 to 50.0 mass% relative to the total coating composition.

6. 6. The coating composition according to claim 5, wherein the urethane oligomer (b3) is a urethane (meth)acrylamide oligomer.

7. A non-adhesive coating layer obtained by polymerizing the coating composition according to any one of claims 1 to 6 with light and / or heat.

8. 7. An adhesive coating layer obtained by polymerizing the coating composition according to any one of claims 1 to 6 with light and / or heat.

9. A pressure-sensitive adhesive sheet comprising the coating layer according to claim 7 or 8 on one or both sides of a film-like and / or sheet-like substrate.

10. A laminate comprising the coating layer according to claim 7 or 8 on one or both sides of a film-like and / or sheet-like substrate.

11. 9. An optical laminate comprising the coating layer according to claim 7 or 8 on one or both sides of a film-like and / or sheet-like substrate, and having a total light transmittance of 80% or more.

12. A laminate for flexible devices, comprising the coating layer according to claim 7 or 8 on one or both sides of a film-like and / or sheet-like substrate.

13. A surface protective laminate comprising the coating layer according to claim 7 or 8 on one or both sides of a film-like and / or sheet-like substrate.

14. A laminate for displays, comprising the coating layer according to claim 7 or 8 on one or both sides of a film-like and / or sheet-like substrate.

15. The laminate according to any one of claims 10 to 14, wherein the film-like substrate is any one of films selected from a polyester film, a polycarbonate film, a fluororesin film, a polyimide film, a triacetyl cellulose film, an acrylic film, a polystyrene film, a polyvinyl chloride film, a polyvinyl alcohol film, and a nylon film.